The economic research guardian (Weissberg SRL, 2011)
The journal encourages the submission of theoretical and empirical research papers in the following areas of economics: Mathematical and Quantitative Methods for Economics, Public Economics, Health, Education, and Welfare, Labor and Demographic Economics, Economic Development, Technological Change, and Growth, Cultural Economics; Economic Sociology; Economic Anthropology--Publisher's website.